IMPACT OF GHOST KITCHEN TOWARDS CONSUMER BEHAVIORAL INTENTION DURING MOVEMENT CONTROL ORDER - Mohd Syafiq Othman; Norfezah Md Nor; Wan Noramira Wan Rosdi (Journal of Islamic, Social, Economics and Development, 2021)
The coronavirus pandemic is likely to permanently change dining habits of Asian consumers, particularly Malaysian Consumer, where a Ghost Kitchen or Cloud Kitchen or Virtual kitchen is becoming their main preference. Therefore, the purpose of this study is to determine the consumers’ behavioral intention to use ghost kitchen service based on decomposition of e-selfqual theory based. A quantitative research methodology via online survey was performed. A nonprobability sampling technique of 200 valid respondents’ answered the survey. The data was then, analysed using SPSS version 21. The multiple regression result showed that more than 62% of perceived control, convenience and service fulfilment influenced the consumers toward ghost kitchen usage. Thus, the result may serve as a groundwork for creating guideline for ghost kitchen set up and operation among food businesses. Moreover, this fulfilling the research gap which is crucial in strengthening food businesses’ economy in the post COVID-19 challenges.